SAGO STARCH AND SODIUM ALGINATE AS NATURAL CROSSLINKING FOR CAPSULE ALTERNATIVES - Harimurti, Sabtanti; Mulyanti, Amelia Nur'afni; Kusnindyasita, Anisa; Widada, Hari; Febriansah, Rifki; Suwanda, Totok; Muhtadi, Muhtadi (Jurnal Farmasi Sains dan Praktis, 2023)
Capsule shells are generally made from gelatin. The gelatin that is spread in the world is commonly derived from pigs. This animal is forbidden to be consumed by Muslims. This issue is due to the halal aspect. Sago starch and sodium alginate are halal materials that are capable of gelatinizing. This property made it able to be molded as a capsule. This research aims to determine the formula of sago and sodium alginate as a capsule and the evaluation. Three formulas were made with the ratio of sago and sodium alginate 100%: 0% (formula 1), 50%: 50% (formula 2), and 0%: 100% (formula 3). The capsule was manually molded using a food-grade stainless steel capsule mold. The size of the capsule, weight uniformity, swelling, and disintegration time were determined for a physical evaluation. SLD was used to determine the best formula, and the validation was done using One-sample T-test. The evaluations of the capsule shell were found ranged as follows: the size specifications were 21-22 mm, the body diameter was 6.1-7.2 mm, the cap diameter was 13.6-13.8 mm, weight uniformity was 0.10-0.26 gram, the swelling test was 433-1583%, and the disintegration time was 10.20-14.43 minutes. The best formula based on the SLD of the experiment was formula 3, which are two parameters that met the requirements, i.e., swelling and disintegration time. The sago and sodium alginate were crosslinked, and the capsule was made. However, the performance dislike of gelatin capsules. Continued research shall be done to find the optimum formula and its characteristics for alternative material on halal capsules.